Sexual risk behaviour among HIV-positive individuals in clinical care in urban KwaZulu-Natal, South Africa. - Kiene, Susan M; Christie, Sarah; Cornman, Deborah H; Fisher, William A; Shuper, Paul A; Pillay, Sandy; Friedland, Gerald H; Fisher, Jeffrey D (AIDS (London, England), 2006)
We assessed the incidence and predictors of unprotected sex among 152 HIV-positive patients in clinical care in KwaZulu-Natal, South Africa. Nearly 50% were sexually active; 30% of those reported unprotected sex. Alcohol use during sex, reporting forced sex, sex with a perceived HIV-positive partner, and sex with a casual partner predicted more unprotected sex, whereas HIV status disclosure was related to less unprotected sex. These findings highlight the need for linking HIV prevention and care in Africa.
Keywords: Adolescent; Adult; Female; HIV Seropositivity; Humans; Incidence; Male; Middle Aged; Sexual Partners; South Africa; Unsafe Sex; Urban Health